Back‐arc magma processes in the Okinawa Trough: new insights from textural and compositional variations of plagioclase in basalts. (22nd January 2016) - Lai, Zhiqing; Zhao, Guangtao; Han, Zongzhu; Liu, Bo.; Bu, Xuejiao; Leng, Chuanxu
Abstract: The evolution of magma during ascent through the crust in the region of the Okinawa Trough is recorded by its mineralogy. In this study, we utilized the characteristics of plagioclase minerals in basaltic magma to deduce magma generation processes, by examining (via back‐scattered electron images) the compositional features of plagioclase phenocrysts in basalts dredged from the middle and southern portions of the Okinawa Trough, which provided a detailed account of the evolution and crystallization of the magma. The crystallization and evolutionary histories of magmas from the middle Okinawa Trough are distinct from those in the southern Okinawa Trough. In the middle Okinawa Trough, we identified seven textural varieties of plagioclase: homogeneous‐core, fine oscillatory‐zoned, core‐sieved, mantle‐sieved, patchy‐core, glomerocrystic and microlitic. Anorthite (An) contents in the cores of plagioclase crystals are 80–87%, while concentrations of Fe, Mg and Sr vary more strongly, especially in patchy‐core plagioclase. The homogeneous‐core, fine oscillatory‐zoned and glomerocrystic plagioclase crystallized in deep‐seated chambers. In contrast, the core‐sieved, mantle‐sieved and patchy‐core textures developed when magmas ascended slowly and were injected into shallow chambers, during which plagioclase was resorbed and dissolved due to decompression. In the southern Okinawa Trough, homogeneous‐core plagioclase crystallized when magma ascended rapidly through deep conduits and was injected into a shallow chamber; under these conditions, only homogeneous‐core and core‐sieved plagioclase phenocrysts crystallized in the shallow chamber. The core of homogeneous‐core plagioclase (An86 –An93 ) was partially resorbed and contaminated by crustal material. Degassing and undercooling promoted the rapid crystallization of microlitic plagioclase, especially in the outermost rims, during and after the extraction of magma from shallow chambers, in both the middle and southern Okinawa Trough. Copyright © 2016 John Wiley & Sons, Ltd.